The Effect of Ploidy on the Brain Cellular Composition of Sterlet Fish - Lernhardt, Tobias (Jihočeská univerzita, 2023)
The aim of this thesis was to determine whether the genome size (diploidy vs. triploidy) of a sterlet (Acipenser ruthenus) could affect the number and density of cells housed in their brains. In order to determine this correlation, we quantified the total brain cell counts and neurons using the Isotropic Fractionation. We then compared the values of 2n males, 2n females, 3n males and 3n females to determine whether a combination of ploidy and sex yielded higher brain cell counts.
The Effect of Ploidy on the Brain Cellular Composition of Sterlet Fish
N/A
Keywords: sterlet; comparative neurobiology; karyotype; ploidy; isotropic fractionation; genome size; genome; neuronal density; triploid; diploid; dimorphism; Acipenser ruthenus; sterlet; comparative neurobiology; karyotype; ploidy; isotropic fractionation; genome size; genome; neuronal density; triploid; diploid; dimorphism; Acipenser ruthenus